Aktivitas Komunikasi Pimpinan Dalam Organisasi - Ayu Anda; Alfian Alfian; Mulyanti Syas (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
One of the keys to the success of an organization is the existence of an effective communication process, both vertically and horizontally. Organizational leaders need to cultivate a communication culture so that the organization can run well. One part of the government organization in Bukittinggi City, West Sumatra is the public relations department. Communication activities in the organization start from intrapersonal, interpersonal, and group communication. The communication activity carried out by the leader is a communication management process. This article describes the results of research on communication activities carried out by the head of the public relations department (Head of Public Relations), ranging from intrapersonal, interpersonal and group communication. This research is a descriptive qualitative research with case study method. Data were collected through observation and interviews. The findings of this study are that the Head of Public Relations has carried out communication management starting from the intrapersonal, interpersonal and group communication stages. The three stages of communication have been carried out, but there are still obstacles, both internal and external, including time constraints and high work activities.